Sustaining Investment in Innovation in Oil Rich Gulf Countries Amidst Falling Oil Prices - Al-Sabah, Meshaal Jaber Al-Ahmad; Palliam, Ralph (Consilience, 2017)
Oil rich Gulf Countries have identified all forms of sustainability as key drivers of innovation. Therefore innovating for sustainability is critical for an economy’s political legitimacy, socio-economic reputation, and ecological performance. Sustaining investment in innovation requires an understanding of returns or payoffs accruing to an investment in innovation. Sustainable development is fraught with challenges particularly when an economy’s growth is linked to a single resource. Research and development together with productivity growth rates have become innovation indicators and continue to raise questions about their interpretation and implication. In resource-laden rich countries the challenge is further exacerbated by inflows accruing from benevolent government subsidies. This empirical study reviews the variables for policy formulation associated with innovation in the six resource-rich oil countries of the Gulf and considers its determinants. Negative relationships between resource abundance and poor economic performance have often been empirically established, providing support for the “resource curse” hypothesis. The culture of governance, norms, and values that pervade oil-rich countries become key determinants of their economic success. The primary purpose of this study is to determine the factors associated with sustainable innovation in the Gulf and to address the concerns related to the governance of resources that necessitate further innovation.